Conflicting priorities: Observation of medicine administration. Issue 19 (10th July 2018) - Alteren, Johanne; Hermstad, Marit; White, Jo; Jordan, Susan
Abstract : Aims and objectives: To identify sources of interruptions and distractions to medicine administration rounds in hospitals. Background: Nurses are frequently interrupted during medicine administration. There is no systematic description of nurses' behaviours and interruptions during administration of medicines to patients. Design: Exploratory nonparticipant observational study. Methods: Three hundred and fifty‐one episodes of medicine administration with 32 nurses from three hospitals in Norway were observed using paper‐based observation grids between December 2013 and March 2014. Results: Nurses were frequently interrupted and distracted, mainly by nurses and other healthcare professionals. One‐third of the nurses interrupted their medicine administration: They prioritised helping patients with direct patient care. When the nurses were interrupted, they left the round and re‐entered the procedure. Even so, they managed to refocus and continue to administer the medicines: Interruptions and disturbances made little difference to most behaviours and actions, possibly because nurses double‐checked more frequently. Some differences were seen in behaviours potentially affecting the safety of the medicine administration, such as leaving medicines at the bedside and not helping patients take their medicines. Some interruptions were avoidable, such as those by other nurses and professionals. Conclusions: This study offers insights into nurses' behaviours and actions when they are interrupted and distracted during medicine administration. The findings highlight a conflict for nurses administering medicines. Nurses are forced to prioritise between two important activities: direct patient care and medicine administration. Management and education providers need to recognise that nurse interrupting each other is a potential threat to patient safety. Relevance to clinical practice: Our data indicate that nurses and other healthcare professionals should be warned not to interrupt colleague administering medicines and managers should ensure other staff are available to respond to patients' immediate needs during medicine rounds.